Seizure Prediction With HIVE-CODAs: The Hierarchical Vote Collective of Domain Adaptation Methods - Peng, Peizhen (Frontiers in Physics, 2022)
Epileptic seizure prediction is one of the most used therapeutic adjuvant strategies for drug-resistant epilepsy. Conventional methods are usually trained and tested on the same patient due to inter-individual variability. However, the challenging domain shift problem between different subjects remains unsolved, resulting in a low prevalence of clinical application. In this paper, a generic model based on domain adaptation (DA) techniques is proposed to alleviate such problems. Ensemble learning is employed by developing a hierarchical vote collective of seven DA modules over multi-modality data, such that the predictive performance is improved by training multiple models. Moreover, to increase the feasibility of its implementation, this work mimics the data distribution of clinical sampling and tests the model under this simulated realistic condition. Based on the performance of seven subnetworks, the applicability of each DA algorithm for seizure prediction is evaluated, which is the first study that provides the assessment. Experimental results on both intracranial and scalp EEG databases demonstrate that this method can reduce the domain gap effectively compared with previous studies.